High-Speed Phase Structured Light Integrated Architecture on FPGA - Chen, Zhong; Hu, Tianlong; Hao, Yuya; Zhang, Xianmin (IEEE transactions on industrial electronics (1982), 2024)
Phase-shifting fringe projection profilometry (FPP) in three-dimension (3D) structured light measurement is widely applied in high-accuracy 3D shape measurement scenarios. But motion objects or other dynamic scenarios make the traditional phase-shifting FPP hard to deal with due to its sizable CPU-based execution time. Therefore, an embedded high-speed and high-accuracy phase-shifting FPP system is designed and implemented on FPGAs. The system implements a three-frequency four-step phase-shifting hardware algorithm with RTL-level caching, multi-frame image ping-pong buffering, and data handling, etc. The system exhibits fully-parallel and pipeline processing while behaving with lower resource and power consumption. Measurement experiments indicate that the proposed method can reach high-accuracy real-time 3D shape measurement with a 3D decoding speed of 40.15 fps when the clock frequency is 200MHz, and the image size is 2432×2048.